PEMANFAATAN LIMBAH PENGOLAHAN IKAN ASAP DI PESISIR PANTAI KENJERAN SURABAYA SEBAGAI BAHAN BAKU PAKAN IKAN - Mohammad Mirwan; Nabilla Nur Merliza (EnviroUS, 2022)
Smoked fish waste has a lot of nutritional content to be used as fish feed. The purpose of this study was to determine the potential of processing smoke fish waste into fish feed in the form of fish pellets and to find out the best combination of fish feed from smoked fish waste with other variables as a mixture. The materials used in making pellets, which will later be given to African catfish (Clasias gariepinus), are a combination of smoking fish waste with tofu dregs, organic vegetables, and restaurant waste. The data obtained is an analysis of the proximate content of fish waste that has been processed into fish pellets with various variations, the test values for proximate analysis parameters in the form of protein content, water content, ash content, and fat content. The results showed that in K.2 (a combination of fish smoking waste with organic vegetable waste) was the best combination with the results of the proximate test analysis of protein content parameters of 33.82%; water content of 7.45%; ash content of 9.27%; and fat content of 18.43%. In this case, the results of the K.2 test have met the maximum and minimum levels as a quality requirement for African catfish (Clasias gariepinus) feed concerning SNI 01-4087-2006.